Relation of total antiradical activity and total polyphenol content of sweet cherries (Prunus avium L.) and tart cherries (Prunus cerasus L.) - Silvia MELICHÁČOVÁ; Mária TIMORACKÁ; Judita BYSTRICKÁ; Alena VOLLMANNOVÁ; Juraj ČÉRY (Acta Agriculturae Slovenica, 2010)
In present study the quantification of total phenolics content (TPC), total antioxidant activity (TAA) and their relation in sweet and tart cherries were studied. Aqueous and pure polar solvents were used to compare the yield of present phenolic compounds in prepared extracts. The solubility of phenolics was the most effective in sweet cherry extracts with using of 50 % methanol and in tart cherry extracts with using of 50 % acetone. The yield of TPC of both tested cherry fruit extracts was higher with pure methanol in comparison to pure acetone.